Divided they fall: Fragmented parliaments and government stability - Felipe Carozzi; Davide Cipullo; Luca Repetto (Uppsala University, Department of Economics, 2020)
This paper studies how political fragmentation affects government stability. We show that each additional party with representation in Parliament increases the probability that the incumbent government is unseated by 4 percentage points. Governments with more resources at their disposal for bargaining are less likely to be replaced. When they are, new government leaders are younger and better educated, suggesting instability may induce positive selection. We interpret our results in light of a bargaining model of coalition formation featuring government instability. Our findings indicate that the rising fragmentation in parliaments worldwide may have a substantial impact on stability and political selection.
urn:nbn:se:uu:diva-407544
Keywords: H1; H7; R50; 330; Government Stability; Fragmentation; No-confidence votes; Bargaining; Alignment effect